RANCANG BANGUN VENDING MACHINE MENGGUNAKAN QR CODE BERBASIS MIKROKONTROLER - Rizki Pradana Putra; I Gusti Agung Pt Raka Agung; Pratolo Rahardjo (Jurnal SPEKTRUM, 2019)
One of the technologies that continues to be developed today is automated system technology. An automatic system that has the potential to continue to develop in this modern era is the vending machine. Along with the development of technology, vending machines have begun to be developed using tags / RFID cards (Radio Frequency Identification) in lieu of paper money. The disadvantage of this system is the dependence of machine activation on an RFID tag / card that still has security risks. Therefore, a vending machine will be developed using QR (Quick Response) Code and integrated with an Android-based smartphone instead of RFID. The microcontroller based vending machine system uses a QR Code to work to serve drinks automatically after processing serial data sent by a smartphone through an application that has been designed with Bluetooth communication. Users can register an account on the application and fill in the balance to buy canned drinks at the vending machine.